Zooming in on Dewey, Democracy, and Subjectivity in Postdigital Education - Berg, Dag-Erik (Postdigital science and education, 2024)
Digital tools, such as video conference technology, are currently transforming people’s behaviour, social relations, and learning processes in higher education. But the digital tools used in teaching and learning are also part of a dynamic capitalism. This article focuses on democracy and subjectivity in higher education and outlines a critical approach in this context. I revisit John Dewey’s philosophy to reflect on digital tools and the goals of education in a democratic society. Published more than a century ago, Dewey’s seminal book Democracy and Education is relevant as a constructive approach to combining learning, experience, habits, and tools. Dewey argued that dualisms between mind and matter, knowledge and nature, undermine a democratic society. For Dewey, a society would require communication and the sharing of experiences whilst education would require democratic aims beyond the individual. Yet the contemporary challenges include a ‘digital gaze’ where the technology makes subjects more visible and observed. Foucault’s analytics of power thus becomes a constructive supplement to Dewey’s focus on participation and modes of inquiry to fully examine subjectivity and democracy in postdigital higher education.